Efeito do controle contextual da transformação de função sobre uma resposta de esquiva derivada: um análogo experimental de desfusão cognitiva - Mello, Matheus Henrique de Souza (2022)
The goal of this study was to build an experimental analogue of the cognitive defusion procedure, an Acceptance and Commitment Therapy (ACT) therapeutic technique. To achieve that, we sought to establish variables with the effect of contextual control over the occurrence and non-occurrence of stimuli function transformation, since, according to the literature, this is the functional relation underlying this intervention. Three equivalence classes were established (A1B1C1D1; A2B2C2D2; A3B3C3D3). An avoidance response under the control of the aversive function of D3 was established. A yellow context was correlated to the positive reinforcement of the responses to C1 and C2 coherent to their derived functions (Fusion Context), while a purple context was correlated to a positive reinforcement of a response to C1 and C2 alternative to their derived functions (Defusion Context). The analog of cognitive defusion consisted of verifying the effect of presenting and removing of Fusion and Defusion Context on the occurrence of avoidance derived from the D3 stimulus. Two experiments were conducted and, in each one, only one participant showed the hypothesized behavior pattern. Conceptual implications, clinical ramifications and future directions were discussed